Desempenho de mecanismos sulcadores de semeadora-adubadora sobre os atributos físicos do solo em várzea no comportamento da cultura da soja (Glycine Max L). - Vizzotto, Vandro Rogerio (2014)
Soybeans are very beneficial in rotation to rice in lowland areas, but one of the limiting factors on the crop in lowland areas is the soil compaction. The objective of this study was to evaluate the effect of furrow mechanisms for soybean driller on the depth of seed placement, the speed, alteration in the physical soil attibutes, on the alteration of the drawbar force, on the fuel consumption and the percentage of tractor tire slip. The experiment was conducted in 2012/ 13 growing season, in Santa Maria, RS Brazil in albaqualf soil Planossolo eutrophic halico Paludalf, Vacacai unit. Soybeans were seeded in November 28, 2012 with a 16.7 seeds.m-1 rate. The treatments were: T1= flat opener disc (DL) and + double disc furrow in the deposition of fertilizer; T2 = DL and + turbo disc (DT); T3 = DT + DT; T4 = DL + shank (HS) and T5 = DL + HS and set covering wheels. The experimental was arranged in a randomized block with five replications. Plots included six soybeans rows spaced by 0.5 m, with 40 m length with a total area of 120 m2. Regarding the depth of deposition of the seed, shank opener showed higher values than the other treatments due to the opening caused by the same time of planting. Soybens emerged faster with shank + set of covering wheels. The planter working in depth reduced soil compaction, increased fuel consumption, tractor tire sliping and traction demand. The shank type mechanism showed greater infiltration of water into the soil, improving drainage and soil aeration.